DESKRIPSI KESALAHAN SISWA SMAN 3 PONTIANAK DALAM MENYELESAIKAN SOAL STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR - Mawarni, Ika; Melati, Husna Amalya; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research was low student achievment, and there were still many students who had difficulty in solving the problems of atomic structure and periodic elements system. This study was conducted to determine the errors and causes of errors made by students of tenth grade IPA of SMA Negeri 3 Pontianak in solving the problems of atomic structure and elements periodic system. The method of this research was descriptive research. The subjects in this study were 37 students of class X IPA 6 SMA Negeri 3 Pontianak. Essay-based test and free-guided interviews were used to collect the data. The results showed that the percentage of understanding essential concepts, understanding the relationship between concepts and understanding the use of concepts to solve problems were 76%, 22% and 2% respectively. There were several causes of students' error. Students did not understand the preresquisite concept and which concept to solve the problems. Students were also careless of reading and found so hard to concentrate which lead them to make mistakes. Moreover students had poor skills at managing time in learning. Keywords: Description, Error, Cause of Error, Atomic Structure, Elements Periodic System